Manajemen Pelatihan: Pengembangan Bahan Ajar Digital Menggunakan Google Sites Dan Youtube Pada Materi Pembuatan Kuis Interaktif Untuk Pembelajaran - Waritsman, Arsyil; Hariyanti, R A Mustika; Japar, Japar (Inovasi: Jurnal Diklat Keagamaan, 2024)
This research was conducted to produce digital teaching materials using Google Sites and YouTube on Interactive Quiz material for use in Learning Multimedia Training. The type of study carried out was research and development (R & D) using the ADDIE model. The subjects in this research were 35 Islamic School Teachers in the Maluku Province. The instruments used in data collection include validation sheets for teaching materials, assessment sheets for the practicality of teaching materials, multiple choice questions for knowledge tests, and practical assessment rubrics for skills tests. Teaching materials are said to be valid if the results of the expert's assessment of the teaching materials are in the minimum good category. Teaching materials are said to be practical if the results of the teacher's and trainee's assessment of the teaching materials are in the minimum good category. Digital teaching materials are said to be effective if 85% of training participants have a knowledge score of more than or equal to 70 and all participants can create projects in the form of creating online quizzes using Quizizz. This research produces digital teaching materials using Google Sites and YouTube interactive quiz materials that meet the requirements for validity, practicality, and effectiveness. The contribution of this research is that the training teaching materials produced can be recommended to be used as a learning resource for multimedia learning training. Apart from that, the results of this research can also provide information about how to produce quality teaching materials that meet training standards.